Challenging the Raison d’etre of Internal Devaluation in the Context of the Greek Economy - Alexiou, Constantinos; Nellis, Joseph G. (Panoeconomicus, 2013)
This paper provides a critical assessment of the austerity measures that are being implemented in the crisis-stricken countries of the Eurozone, and in particular, the implications of internal devaluation for the Greek economy. The theoretical underpinnings and phases of internal devaluation are explored. A detailed statistical analysis of key macroeconomic indicators pertaining to the Greek economy is carried out. Alternatives to internal devaluation are proposed in this paper, laying the foundations for a reassessment of the policy of austerity and the implications for recovery and sustainability of economic activity in Greece and other countries of the Eurozone.Key words: Internal devaluation, Greek economic crisis, Austerity, Eurozone.JEL: E62, E66.